KONTRIBUSI KEPEMIMPINAN 5.0 TERHADAP IMPLEMENTASI SUPERVISI AKADEMIK DALAM PENGUATAN LITERASI EKOTEOLOGIS SISWA MADRASAH ALIYAH NEGERI SE-KOTA BOGOR - Muhamad Robie Awaludin S; Ima Rahmawati; Bintang Caraka Soeganda (Institut Agama Islam Sahid (INAIS) Bogor, 2026)
This study aims to examine the contribution of Leadership 5.0 to the implementation of academic supervision in strengthening students’ ecotheological literacy at State Islamic Senior High Schools (Madrasah Aliyah Negeri) in Bogor City. A quantitative approach with a correlational survey design was employed. The population comprised 142 teachers and 1,318 students from MAN 1 and MAN 2 Bogor City, with a sample of 105 teachers and 298 students selected through proportional random sampling. Data were collected using Likert-scale questionnaires and analyzed using Jamovi, including descriptive statistics, reliability testing, linear regression, and path analysis. The findings indicate that Leadership 5.0 has a positive and significant effect on academic supervision, while academic supervision significantly contributes to strengthening students’ ecotheological literacy. Moreover, academic supervision mediates the relationship between leadership and ecotheological literacy, indicating that leadership influences students’ ecotheological literacy indirectly through supervised pedagogical practices. These results highlight the importance of value-oriented, collaborative, and adaptive leadership, along with academically developmental supervision, in reinforcing ecotheological literacy. The study provides empirical support for integrating leadership and supervision practices to advance ecotheology-based educational goals in alignment with the Indonesian Ministry of Religious Affairs’ Priority Programs 2025–2029.